Employee job performance in higher education institutions as affected by academicians' attitudes towards motivation, self-efficacy, and qualities during covid-19 pandemic - Mohd Firdaus Kozako, Intan Nurul’ain; Suhaimin, Mohd Faiez; Mohd Pauzi, Nooradzlina; Amran, Atiela; Aminuddin, Azwan Shah (2023)
The purpose of this study is to identify the elements that have the greatest influence on job performance, motivation, and self-efficacy as they relate to telework. This study using a sample from 13 branches of Universiti Teknologi MARA (UiTM), Malaysia. A total of 369 samples were drawn at random among 8788 academic employees. To complete this study, every aspect of telework was evaluated in connection to job performance utilising quantitative methodology. The gathered data was analysed using SPSS, Version 22. Findings show that all categories have a strong positive link with job performance, with the exception of telework self-efficacy and telework characteristics, which influence job performance among academic employees at UiTM. Future research is advised to evaluate the functions of telework self-efficacy towards job performance among UiTM management personnel because it has been demonstrated that these variables have a limited influence among UiTM academicians. The identification of efficient telework arrangements and performance management measures may assist organisations in optimising their telework policies and enhancing employee job performance, while also maintaining employee well-being. This paper is funded by Geran Dalaman Dana Universiti Teknologi MARA.